Perception of Local Journalists in West Nusa Tenggara about the Media Industry - Nur , Muhammad Jamiluddin; Diyah Indiyati; Shinta Desiyana Fajarica (Jurnal Spektrum Komunikasi, 2023)
This study aims to determine the perceptions of local journalists in West Nusa Tenggara (NTB) province, especially Lombok. This type of research is qualitative and the method used is phenomenology. The process of collecting research data was carried out through observation, and in-depth interviews. The researcher also conducted documentation and literature studies relevant to the research. The researcher analyzed the stages of organizing data, noting important points, describing meanings for informants, grouping statements into several units, developing descriptive text, detailing the experiences of informants more deeply through descriptions, and drawing conclusions. This research found that journalists who work in online media think that the print media industry still has a special niche of customers from the educated to government employees, but if they are not creative then print media will decrease. On the other hand, print media journalists feel that the print media industry will survive as long as regulations regarding local government advertising spending do not change. This regulation benefits print media because the value of their advertising partnership is much higher than online media. This research also found that print media journalists understand the condition of their company's dependence on local government and this relationship pattern is not sustainable. Meanwhile, online media journalists understand that their work culture in this industry demands more work while there is very little support for social and health insurance, especially for those who are contributing journalists.